World Wide Web audio: ensuring adequate hardware and software configurations - Ang, Minni Kim Huai; Othman, Abu Talib; Tee, Elok Robert (Faculty of Computer Science and Information Technology, University of Malaya, 1996)
As Client machines need to be properly configured with the correct hardware and software to playback the many different audio file formats available, a discussion of how to configure client machines is given.